2016
DOI: 10.1002/cbf.3172
|View full text |Cite
|
Sign up to set email alerts
|

Targeting ROR1 inhibits the self‐renewal and invasive ability of glioblastoma stem cells

Abstract: Glioblastoma is the most malignant of brain tumours and is difficult to cure because of interruption of drug delivery by the blood-brain barrier system, its high metastatic capacity and the existence of cancer stem cells (CSCs). Although CSCs are present as a small population in malignant tumours, CSCs have been studied as they are responsible for causing recurrence, metastasis and resistance to chemotherapy and radiotherapy for cancer. CSCs have self-renewal characteristics like normal stem cells. The aim of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 34 publications
(75 reference statements)
0
20
0
Order By: Relevance
“…The invasion capabilities of GSCs also contributes to the initiation of cancer metastasis (31). As such, the anti-invasive potential of CK on GSCs from U87MG and U373MG cells was evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…The invasion capabilities of GSCs also contributes to the initiation of cancer metastasis (31). As such, the anti-invasive potential of CK on GSCs from U87MG and U373MG cells was evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, the data reported on by Liu et al suggested that silencing ROR1 critically associated with the inhibition of cell growth and the induction of cell apoptosis in lung cancer via PI3K/AKT/mTOR signaling pathway . In glioblastoma, Jung et al illustrated that knockdown of ROR1 severely inhibited tumor stemness, sphere formation, migratory action and invasive ability . In addition, a monoclonal anti‐ROR1 Fab antibody could inhibit tumor cell proliferation and migration, while inducing tumor cell apoptosis .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it was shown that down-regulation of Ror1 suppressed the expression of EMTrelated genes and the migratory and invasive abilities of the tumour. The results of this study indicated that targeting Ror1 could induce differentiation of cancer stem cells (CSCs) and inhibit metastasis in glioblastoma 15 . In a recent report, it was also shown that siRNAs targeting Ror1 in CLL induced apoptosis and a small molecule inhibitor, Ror1 tyrosine kinase inhibitor dephosphorylated Ror1, down-regulating the activated PI3K/AKT/mTOR signaling pathway and inducing specific apoptosis of CLL cells 66 .…”
Section: Discussionmentioning
confidence: 87%
“…Although, Ror1 does not express itself virtually in all normal adult tissues, it re-expresses in many tissues during some B-cell malignancies, and various cancer cell lines 6, 8, 15, 16 . Ror1 was significantly more expressed in various tumours such as acute lymphocytic leukemia, renal carcinoma, breast cancer, lung cancer, adenocarcinoma and melanoma 1621 .…”
Section: Introductionmentioning
confidence: 99%